Futile therapy in the conditions of the Covid-19 pandemic - Gorczyca, Kamila; Podgórska, Klaudia; Puła, Aleksandra; Artykiewicz, Klaudia; Krzysiek, Urszula; Kozieł, Paweł; Grodkiewicz, Maria; Czarkowski, Marcin; Słupczyńska, Aleksandra; Urbaś, Weronika (Journal of Education, Health and Sport, 2022)
Futile therapy is the prolonged maintenance of organ function. This process in this case does not bring therapeutic benefits, and its task is to maintain the failed organs. The article aims to present the differences between influenza and Covid-19 and to draw attention to the problem of the futility of therapy in the context of a pandemic.